Augmented reality for virtual practical learning of EDM wire cut maintenance / Abdul Rahman Hemdi, Noorzalifah Tongal and Rohidatun Mahmod@Wahab - Hemdi, Abdul Rahman; Tongal, Noorzalifah; Mahmod@Wahab, Rohidatun (Universiti Teknologi MARA, Pulau Pinang, 2022)
This research aims to develop 3D augmented reality (AR) for virtual learning of EDM wire cut machine maintenance. The two maintenance processes such as replacement of filter pressure and upper electrode pin checking was selected as content of AR application. The 3D model of EDM wire cut was designed using Solid Works and then embedded into Unity 3D software for AR development. The developed AR consists of three main elements such as GUI page, maintenance filter pressure GUI page and maintenance upper electrode pin GUI page. Instead of 3D visualization, the developed AR also consists of a clear step-by-step instruction maintenance procedure. In addition, the user feedback is also gathered to verify the usability and functionality of the developed AR application. The 25 respondents among Mechanical Engineering students were given the experience of using the developed AR and then answering the questionnaire. Based on the findings, the respondents agreed that developed AR can be used for training and learning of EDM wire cut maintenance.